Older people's perceptions of a multifaceted Podiatry medical intervention to prevent falls - Menz, H.; Spink, M.; Landorf, K.; Hill, Keith; Lord, S. (American Podiatric Medical Association, 2013)
Background: Falls are common in older people and are associated with substantial health-care costs. A recent randomized controlled trial of a multifaceted podiatric medical intervention demonstrated a 36% reduction in the fall rate over 12 months. We evaluated the acceptability of and levels of satisfaction with this intervention in the older people who participated in the trial.Methods: Participants allocated to the intervention group (which included a home-based program of foot and ankle exercises, assistance with the purchase of safe footwear when necessary, and provision of prefabricated foot orthoses) completed a structured questionnaire 6 months after they had received the intervention. The questions addressed participants’ perceptions of their balance and foot and ankle strength, the perceived difficulty of the exercise program, and the degree of satisfaction with the footwear and orthoses provided.Results: Of 153 participants, 134 (87.6%) attended the 6-month follow-up assessment and completed the questionnaire. Most participants perceived improvements in balance (62.7%) and foot and ankle strength (74.6%) after 6 months of performing the exercises, and 86.6% considered the difficulty level of the exercises to be “about right.” Most participants reported that they were somewhat or very satisfied with the footwear (92.3%) and orthoses (81.6%) provided.Conclusions: The multifaceted podiatric medical intervention used in this trial was generally perceived to be beneficial and demonstrated high levels of satisfaction among participants. Further research is now required to evaluate the feasibility of implementing the intervention in a range of clinical practice settings.